2009
DOI: 10.1007/s12544-009-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

In-depth evaluation of the effects of an automatic emergency call system on road fatalities

Abstract: Purpose This study aimed to evaluate the effects of an automatic emergency call system on accident consequences in Finland (ex-ante evaluation). In addition, the effects of the system on emergency response times and the effects of realtime information about the accident location were assessed. Methods The evaluation utilised in-depth accident reports collected by the road accident investigation teams during the period [2001][2002][2003]. The time delay between the accident occurrence and notification of the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…An evaluation in Korea estimated that if all vehicles were equipped with ACN systems, 9–15 % of crash-fatalities could be prevented on Korean highways (Jeong et al 2014). A study in Finland examined an ACN system and concluded that the system prevented 4–8 % of road fatalities (Sihvola et al 2009). Another study estimated the effects of an ACN system employed across the US and reported that such a system could save 2–6 % of fatalities each year (Clark & Cushing 2002).…”
Section: Resultsmentioning
confidence: 99%
“…An evaluation in Korea estimated that if all vehicles were equipped with ACN systems, 9–15 % of crash-fatalities could be prevented on Korean highways (Jeong et al 2014). A study in Finland examined an ACN system and concluded that the system prevented 4–8 % of road fatalities (Sihvola et al 2009). Another study estimated the effects of an ACN system employed across the US and reported that such a system could save 2–6 % of fatalities each year (Clark & Cushing 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The most successful interventions to prevent RTA death are speed and drink-driving enforcement [26]. However, RTA deaths can also be reduced by the availability of fast and reliable emergency services in rural areas, the use of telemetric systems including automated accident notification systems connected to emergency services and post traumatic rehabilitation services to prevent complications [40, 41]. These interventions should be prioritized at all levels along with bicycle and motorcycle helmet use and seat-belt use for front and rear passengers.…”
Section: Discussionmentioning
confidence: 99%
“…However, that finding, applied to our data set, would have impacted less than 1% of all fatalities. 21 Trauma mortality has been reported to increase in proportion with the length of EMS response time 17,[22][23][24] and duration of hospitalization, 25 although the data are controversial. 26 Ultimately, the impact of transport time on mortality may be marginal, and model-dependent.…”
Section: Discussionmentioning
confidence: 99%